A Base Isolation System for Developing Countries Using Discarded Tyres Filled with Elastomeric Recycled Materials. Issue 2 (17th February 2017) - Hadad, Houman A.; Calabrese, Andrea; Strano, Salvatore; Serino, Giorgio
Abstract : This article studies the performance of economic base isolators using tyres filled with elastomeric recycled materials. The research was conducted to analyze base isolators to be used in developing nations, where the application of conventional elastomeric rubber bearings due to economic reasons is limited. The tested isolators are made of kart tyres filled with different recycled elastomeric materials and aggregates. Dynamic and static tests proved acceptable vertical to horizontal stiffness ratio of the bearings and shake table tests showed an excellent enhancement of the base isolated structural response compared to the corresponding fixed base structure.